Not sick of basick - 2

Algebra Level 5

Let p ( x ) p(x) be a fourth degree polynomial such that p ( 1 ) = 1 p(1)=1 , p ( 2 ) = 1 2 p(2)=\frac{1}{2} , p ( 3 ) = 1 3 p(3)=\frac{1}{3} , p ( 4 ) = 1 4 p(4)=\frac{1}{4} , p ( 5 ) = 1 5 p(5)=\frac{1}{5} and p ( 6 ) = A B p(6)=\frac{A}{B} .

Find A + B A+B , where A A and B B are coprime.


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Noel Lo
Jul 21, 2015

We can generate an equation:

x p ( x ) = k ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) + 1 xp(x) = k(x-1)(x-2)(x-3)(x-4)(x-5) + 1 .

Sub in x = 0 x=0 we have:

0 = 120 k + 1 0 = -120k+1

So k = 1 120 k = \frac{1}{120} and x p ( x ) = ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) 120 + 1 xp(x) = \frac{(x-1)(x-2)(x-3)(x-4)(x-5)}{120} + 1 .

Sub in x = 6 x=6 we get:

6 p ( 6 ) = 5 ( 4 ) ( 3 ) ( 2 ) ( 1 ) 120 + 1 = 1 + 1 = 2 6p(6) = \frac{5(4)(3)(2)(1)}{120} + 1 = 1+1 = 2

p ( 6 ) = 2 6 = 1 3 p(6) = \frac{2}{6} = \frac{1}{3} .

So a + b = 1 + 3 = 4 a+b =1+3 = \boxed{4}

Ravi Dwivedi
Jul 8, 2015

Moderator note:

Great approach! That's the one that I'm thinking of, which is useful for solving such polynomials following a particular algebraic pattern.

Why is this a level 5 problem? Should be level 4. Regardless, concept employed is neat.

Nishant Sharma - 3 years ago

From the given information, we deduce that p ( x ) p(x) is of the form:

p ( x ) = 1 24 ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) 1 12 ( x 1 ) ( x 3 ) ( x 4 ) ( x 5 ) + 1 12 ( x 1 ) ( x 2 ) ( x 4 ) ( x 5 ) 1 24 ( x 1 ) ( x 2 ) ( x 3 ) ( x 5 ) + 1 120 ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) \begin{aligned} p(x) & = \frac{1}{24} (x-2)(x-3)(x-4)(x-5) - \frac{1}{12} (x-1)(x-3)(x-4)(x-5) \\ & \quad + \frac{1}{12} (x-1)(x-2)(x-4)(x-5) - \frac{1}{24} (x-1)(x-2)(x-3)(x-5) \\ & \quad \quad + \frac{1}{120} (x-1)(x-2)(x-3)(x-4) \end{aligned}

p ( 6 ) = 1 24 ( 4 ) ( 3 ) ( 2 ) ( 1 ) 1 12 ( 5 ) ( 3 ) ( 2 ) ( 1 ) + 1 12 ( 5 ) ( 4 ) ( 2 ) ( 1 ) 1 24 ( 5 ) ( 4 ) ( 3 ) ( 1 ) + 1 120 ( 5 ) ( 4 ) ( 3 ) ( 2 ) = 24 24 30 12 + 40 12 60 24 + 120 120 = 1 5 2 + 10 3 5 2 + 1 = 1 3 \begin{aligned} \Rightarrow p(6) & = \frac{1}{24} (4)(3)(2)(1) - \frac{1}{12} (5)(3)(2)(1) + \frac{1}{12} (5)(4)(2)(1) \\ & \quad - \frac{1}{24} (5)(4)(3)(1) + \frac{1}{120} (5)(4)(3)(2) \\ & = \frac{24}{24} - \frac{30}{12} + \frac{40}{12} - \frac{60}{24} + \frac{120}{120} \\ & = 1 - \frac{5}{2} + \frac{10}{3} - \frac{5}{2} + 1 \\ & = \dfrac{1}{3} \end{aligned}

A + B = 1 + 3 = 4 \Rightarrow A + B = 1 + 3 = \boxed{4}

Moderator note:

There is a much faster way using the Polynomial interpolation - Remainder-Factor Theorem .

Hint: What can we say about x f ( x ) x f(x) ?

Crap. This was too much.

Sorry for my liberal use of words.

Just entered a random answer and got it correct :P

Wanted to see the solution.

Mehul Arora - 5 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...